Unraveling Aesthetics Tapestry: Mapping the Artistic Styles of Young Contemporary Artist in Bandung - Agung, Lingga; Bastari, Rendy Pandita; Gumilar, Ganjar; Lionardi, Angelia; Siswanto, Riky Azharyandi (Institut Seni Indonesia Denpasar, 2024)
Bandung thrives as a city deeply entrenched in its artistic progression, boasting a vibrant array of art institutions, galleries, collectives, and accolades in the axis of Indonesian contemporary art. Despite this flourishing landscape, the divergence of contemporary art from conventional aesthetics poses challenges in garnering public appreciation. Since the early 2000s, Bandung’s contemporary art scene has witnessed a proliferation of innovative expressions influenced by recent aesthetic philosophies, notably postmodernism, and characterized by diverse aesthetic idioms. However, despite these progressive strides, a notable gap persists between contemporary art in Bandung and its local community. This study utilizes qualitative methodologies, including Focus Group Discussions (FGD) and visual analysis, to probe the aesthetic nuances within Bandung’s contemporary art milieu. FGD sessions delve into aesthetic dialogues, institutional dynamics, and community perceptions, while visual analysis deciphers cultural symbols within socio-political contexts. The findings illuminate prevalent themes of parody, pastiche, kitsch, and cultural fusion, indicative of a profound exploration of Indonesian identity amidst the currents of globalization. Bandung young contemporary artists adeptly interweave traditional values with contemporary themes, infusing their works with tradition, religion, and locality elements. While defying rigid categorization, these creations unveil intriguing intersections deserving further scholarly inquiry. This research underscores Bandung’s contemporary art scene as a complex and diverse tapestry shaped by historical, political, and social dynamics. It emphasizes the importance of discursive meaning and social processes within the artistic medium, shedding light on the intricate interplay between artistic innovation and socio-cultural contexts within Bandung’s vibrant art landscape.